Credit Investments in Northern Italian States (17th–18th Centuries) - Lorenzini Marcella (Jahrbuch für Wirtschaftsgeschichte)
This article examines investment opportunities in northern Italian states in the 17th and 18th centuries, with a focus on the private credit market. The research is based on loan contracts drawn up by notaries and on fiscal and administrative documents. Thanks to the service provided by notaries, who operated as informal financial intermediaries, investment in the credit market became accessible even to those unfamiliar with financial activities, including small landowners, artisans, and women. Crucial within this network was the role played by religious institutions, particularly women’s convents, for some of the profits from lending activity represented the main source of income. Although land was the preferred sector in pre-industrial times, this study shows that an increasing amount of capital was invested in private credit networks, which offered higher returns with limited risk, as these loans were always backed by collateral. Within the most dynamic markets, new and innovative instruments were devised, providing great flexibility in terms of collateral, maturity and profitability.